Damping behavior of continuous fiber/metal composite materials by the free vibration method - Botelho, E. C.; Campos, A. N.; de Barros, E.; Pardini, L. C.; Rezende, M. C. (Elsevier B.V., 2006)
Fiber metal laminates (FML) offer significant improvements over current available materials for aircraft structures due to their excellent mechanical characteristics and relatively low density. Non-destructive testing techniques are being used in the characterization of composite materials. Among these, vibration testing is one of the most used tools because it allows the determination of the mechanical properties. In this work, the viscoelastic properties such as elastic (E') and viscous (E) responses were obtained for aluminum 2024 alloy; carbon fiber/epoxy; glass fiber/epoxy and their hybrids aluminum 2024 alloy/carbon fiber/epoxy and aluminum 2024 alloy/glass fiber/epoxy composites. The experimental results were compared to calculated E modulus values by using the composite micromechanics approach. For all specimens studied, the experimental values showed good agreement with the theoretical values. The damping behavior, i.e. The storage modulus and the loss factor, from the aluminum 2024 alloy and fiber epoxy composites can be used to estimate the viscoelastic response of the hybrid FML. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: hybrid; mechanical properties; vibration